The preemptive effect of tramadol and metamizole on the intensity of postoperative pain - Ismet Suljević; Muamer Hadžiavdić; Ismana Šurković; Omer Suljević; Maida Turan; Ehlimana Mušija (Medicinski glasnik, 2020)
Aim: To demonstrate the analgesic effect of preemptively administered tramadol and metamizole on the postoperative pain severity, after an elective operative hysterectomy with adnexectomy. Methods: There were three groups with 30 patients in each group. Patients included in the study were between 45 to 67 years old. They were all in the ASA group II. Randomization was performed in random order according to the regular elective operating program. Patients in Group I received i. m. tramadol 1mg/kg, and in Group II 30mg/kg of metamizole, five minutes before anaesthesia induction. Patients did not receive preemptive analgesia in Group III (control). All patients underwent the same induction anaesthesiology procedure with propofol, fentanyl, tracrium, supplemented with O2, N2O, and sevoflurane at an appropriate dose until MAC 1 was reached. Surgeries lasted for 80-120 minutes. Every patient performed a resting pain assessment 30 minutes after an extubation by Numerical Pain Scale (NPS). Results: We found out that tramadol had a better effect in preemptive analgesia and that the average pain score for Group I was 6.10 (p=0.043). In Group II, it was 7.93 (p=0.022). There is significant difference in pain intensity between patients in the control group, (pain intensity was 9.16), and those who received tramadol and metamizole. There was no significant difference in the intensity of pain when using these two analgesics (p=0.733). Conclusion: The effect of preemptively administered tramadol prior to the introduction of general anaesthesia in postoperative pain is significantly more favourable than the effect of metamizole.
Keywords: analgesia; general anaesthesia; hysterectomy; pain assessment